2002
DOI: 10.1016/s1097-2765(02)00473-2
|View full text |Cite
|
Sign up to set email alerts
|

The Dissociation of Cohesin from Chromosomes in Prophase Is Regulated by Polo-like Kinase

Abstract: The separation of sister chromatids in anaphase depends on the dissociation of cohesin from chromosomes. In vertebrates, some cohesin is removed from chromosomes at the onset of anaphase by proteolytic cleavage. In contrast, the bulk of cohesin is removed from chromosomes already in prophase and prometaphase by an unknown mechanism that does not involve cohesin cleavage. We show that Polo-like kinase is required for the cleavage-independent dissociation of cohesin from chromosomes in Xenopus. Cohesin phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
362
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 411 publications
(372 citation statements)
references
References 31 publications
8
362
0
2
Order By: Relevance
“…Moreover, a recent study suggests that PLK1 is able to phosphorylate Cyclin B1 (Jackman et al, 2003) directly, and that specific phosphorylation cooperated with other signals in the nuclear import of Cyclin protein, a crucial checkpoint for the initiation of mitosis (Yuan et al, 2002). Later in mitosis, PLK1 has been implicated in the regulation of the anaphasepromoting complex (Kotani et al, 1998;Golan et al, 2002), centrosome maturation and destructions of cohesins (Sumara et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study suggests that PLK1 is able to phosphorylate Cyclin B1 (Jackman et al, 2003) directly, and that specific phosphorylation cooperated with other signals in the nuclear import of Cyclin protein, a crucial checkpoint for the initiation of mitosis (Yuan et al, 2002). Later in mitosis, PLK1 has been implicated in the regulation of the anaphasepromoting complex (Kotani et al, 1998;Golan et al, 2002), centrosome maturation and destructions of cohesins (Sumara et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that cohesin dissociates from chromosomes before metaphase, which requires the Plk1 (Sumara et al, 2002). A recent study revealed that Rad21/Scc1 and SA2/ Scc3 are the major targets of Plk1 (Hauf et al, 2005).…”
Section: Mitosis-specific Activity Of Cohesin At the Spindle Polesmentioning
confidence: 99%
“…This population is essential in preventing precocious separation of the sister chromatids and allowing proper chromosome alignment (Vass et al 2003;Vagnarelli et al 2004;. The dissociation of cohesin in prophase requires Polo and Aurora B kinases as well as a number of additional factors that include Wapl Sumara et al 2002;Hauf et al 2005;Gandhi et al 2006;Kueng et al 2006). At the onset of anaphase, cleavage of Scc1/Rad21 by separase drives dissociation of the remaining cohesin and sister chromatid separation ensues (Hauf et al 2001).…”
Section: Introductionmentioning
confidence: 99%